2015
DOI: 10.1002/ece3.1630
|View full text |Cite
|
Sign up to set email alerts
|

Candidate gene–environment interactions and their relationships with timing of breeding in a wild bird population

Abstract: Monitoring and predicting evolutionary changes underlying current environmental modifications are complex challenges. Recent approaches to achieve these objectives include assessing the genetic variation and effects of candidate genes on traits indicating adaptive potential. In birds, for example, short tandem repeat polymorphism at four candidate genes (CLOCK, NPAS2, ADCYAP1, and CREB1) has been linked to variation in phenological traits such as laying date and timing of migration. However, our understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 75 publications
4
57
0
Order By: Relevance
“…, ; Bazzi et al . , ; Bourret & Garant ). Such an among‐species variability in candidate gene diversity could be associated with migratory behaviour and/or geographic distribution.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…, ; Bazzi et al . , ; Bourret & Garant ). Such an among‐species variability in candidate gene diversity could be associated with migratory behaviour and/or geographic distribution.…”
Section: Introductionmentioning
confidence: 97%
“…, ; Bazzi et al . ; Bourret & Garant ). Moreover, we tested the hypothesis that species breeding at more northern latitudes have longer Clock alleles.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Adcyap1 polymorphism has been mainly linked to dispersal (Chakarov et al ., ) or migratory behaviour, and in some species it predicts migration distance or breeding latitude among populations (Mueller et al ., ; Peterson et al ., ; Mettler et al ., ; Bazzi et al ., ). To date, only one study (Bourret & Garant, ) disclosed a complex genotype by environment interaction on breeding date: in female tree swallows ( Tachycineta bicolor ), Adcyap1 length polymorphism did not predict laying dates per se (see also Chakarov et al ., ), but depending on the breeding latitude (Bourret & Garant, ). We note that a lack of the association between length polymorphism in the Adcyap1 gene and breeding phenology can be explained by the observed genetic variability of this gene, which is markedly lower than that disclosed in other species (Chakarov et al ., ; Bourret & Garant, ; Bazzi et al ., , b).…”
Section: Discussionmentioning
confidence: 99%
“…A flourishing body of studies has recently identified some of these phenological genes, conserved among phylogenetically distant taxa, whose polymorphism has been invoked to explain differences in the photoperiodic responses among individuals and populations (Johnsen et al ., ; O'Malley & Banks, ; O'Malley, Ford & Hard, ; Bourret & Garant, ; Saino et al ., ). Although polymorphism can be found in several gene regions, most of such studies focused on the presence of tandem repeats which are involved in their regulatory functions, and suggested that their length polymorphism is, at least partly, controlling inter‐individual variability in phenological traits (Kashi, King & Soller, ; Li et al ., ; Fondon et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation